The Application the Drill Method as an Effort in Improving Mathematics Learning Outcomes of Elementary Level Students - Ali Nurwidiyanto; Martha Betaubun; Dewi Puji Rahayu; Eli Ngatripah (Universitas Muhammadiyah Enrekang, 2023)
Learning mathematics is essentially doing mental activities. In mathematics learning, students are required to prepare mentally in the process of receiving new knowledge. Facts in the field show that the lack of use of creative and innovative learning methods in the mathematics learning process has an impact on the low mathematics learning outcomes of grade V elementary school students. Therefore, this research aims to apply the drill method as one of the creative and innovative methods to improve student learning outcomes. This research is a quantity research by applying pre-experimental design. Using one group pre-test and post-test, this study was conducted on grade V students of SD Negeri 2 Merauke in the 2022/2023 academic year. The total sample in this study was 32 students with the data collection method being a test. The results showed that there was a very significant improvement in student learning outcomes. The increase in the percentage of the average score of student learning outcomes from the previous pre-test of 56.78 increased in the post-test of 84.65. However, we cannot ignore the obstacles that occur. Some obstacles when implementing the drill method are inhibiting the development of students' initiative abilities, the formation of rigid and inflexible habits, the emergence of verbalism, and the emergence of boredom and boredom. For this reason, teachers must implement the drill method in a fun way, for example through games or combined with other methods.